2023
DOI: 10.4103/jpbs.jpbs_174_23
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Flexural and Compressive Strengths of EQUIA, GC Gold Hybrid, and Conventional GIC Restorative Materials

Abstract: Objectives: This in vitro research was performed to assess the flexural and compressive strengths of EQUIA, GC Gold Hybrid (GH), and conventional glass ionomer cement (GIC) restorative materials. Materials and methods: This study compares three restorative Materials: group I—EQUIA Forte GIC, group II—GC GH, and group III—conventional GIC for compressive and flexural strength evaluation. With a specially made Teflon mold, thirty-six cylindrical test spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Joshi et al compared the compressive and flexural strengths of three different glass ionomer restorative materials. As a result of the study, it was observed that Equia Forte was the material with the highest compressive and flexural strength [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joshi et al compared the compressive and flexural strengths of three different glass ionomer restorative materials. As a result of the study, it was observed that Equia Forte was the material with the highest compressive and flexural strength [ 38 ].…”
Section: Discussionmentioning
confidence: 99%